(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The recent sanction of Law 14,837/2024 represents a significant advance in the way school libraries are designed and operated in Brazil. By redefining the school library as a fundamental cultural equipment for educational development, the law emphasizes the need to democratize access to information and integrate new technologies into the school environment. The research was a literature review on innovation and technology in libraries, focusing on recent studies (2020-2024), based on the analysis of technological solutions present in university libraries for application in school libraries, complying with the principles of the new law. The objective is to extrapolate examples, both national and international, applying these innovative solutions to school libraries.